1992
DOI: 10.1098/rspb.1992.0135
|View full text |Cite
|
Sign up to set email alerts
|

Wolbachiaendosymbionts responsible for various alterations of sexuality in arthropods

Abstract: Rickettsia-like maternally inherited bacteria have been shown to be involved in a variety of alterations of arthropod sexuality, such as female-biased sex ratios, parthenogenesis, and sterility of crosses either between infected males and uninfected females or between infected individuals (cytoplasmic incompatibility). We have characterized several of these microorganisms through partial sequences of the small (16S) and large (23S) subunit ribosomal DNA. All the symbionts identified, which include several cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
148
2
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 413 publications
(154 citation statements)
references
References 28 publications
3
148
2
1
Order By: Relevance
“…This notion was strengthened by the lack of congruence between Wolbachia and phage phylogenies established with the orf7 sequence (ORF Gp3 in our study), suggesting horizontal phage exchange between bacteria co-infecting the same intracellular environment (Bordenstein & Wernegreen 2004;Gavotte et al 2004;Sanogo & Dobson 2004). Since all polymorphic regions found so far in wPip DNA are mobile genetic elements (Sanogo & Dobson 2004;Duron et al 2005), the 'real' Wolbachia genes being monomorphic (Rousset et al 1992;Guillemaud et al 1997;Duron et al 2005), it was proposed that these mobile genetic elements could favour genome fluidity and enhance rapid adaptation, especially in the highly diversified CI system of C. pipiens. For all these reasons we decided to study WO prophage organization and variability in the wPip genome.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This notion was strengthened by the lack of congruence between Wolbachia and phage phylogenies established with the orf7 sequence (ORF Gp3 in our study), suggesting horizontal phage exchange between bacteria co-infecting the same intracellular environment (Bordenstein & Wernegreen 2004;Gavotte et al 2004;Sanogo & Dobson 2004). Since all polymorphic regions found so far in wPip DNA are mobile genetic elements (Sanogo & Dobson 2004;Duron et al 2005), the 'real' Wolbachia genes being monomorphic (Rousset et al 1992;Guillemaud et al 1997;Duron et al 2005), it was proposed that these mobile genetic elements could favour genome fluidity and enhance rapid adaptation, especially in the highly diversified CI system of C. pipiens. For all these reasons we decided to study WO prophage organization and variability in the wPip genome.…”
Section: Discussionmentioning
confidence: 90%
“…However, no polymorphism was observed in strains displaying incompatibilities using the ftsZ gene (Guillemaud et al 1997), driving the authors to conclude that factors other than Wolbachia variants were responsible for incompatibility in this species. Similarly, no polymorphism could be detected either in the 16S rRNA sequences of Wolbachia infecting different C. pipiens subspecies (Rousset et al 1992) or in the fastest Wolbachia evolving gene wsp of mosquitoes sampled worldwide (Duron et al 2005). Recent searches for polymorphism in wPip have produced a few markers, all affecting mobile genetic elements.…”
Section: Introductionmentioning
confidence: 99%
“…These manipulations fall into two classes. Sex-ratio-distorting strains increase the production of daughters at the expense of sons by killing males, feminizing genetic males or inducing parthenogenesis (Rousset et al 1992;Stouthamer et al 1993;Hurst et al 1999). Other strains induce cytoplasmic incompatibility, which (in singly infected diploid hosts) causes a reduction in the viability of o¡spring in crosses between infected males and uninfected females (O'Neill et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…As the ability to induce CI is found in different Wolbachia lineages, it has been suggested that this ability is ancestral (Rousset et al., 1992). Our analysis does not provide clear support for this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…The host reproductive phenotype associated with this origin, that is the host reproductive phenotype ancestral to supergroups A and B, is unknown. It has been suggested that CI is ancestral to all Wolbachia lineages (Rousset, Bouchon, Pintureau, Juchault, & Solignac, 1992; Stouthamer, Breeuwer, & Hurst, 1999). However, to the best of our knowledge, this assertion has never been analyzed using comparative methods.…”
Section: Introductionmentioning
confidence: 99%